Relações retóricas em orações de particípio - Leal, António; Silvano, Purificação; Oliveira, Fátima (Revista da Associação Portuguesa de Linguística, 2016)
The main objective of this work is to describe the semantic values of sentences with clauses of participle with a NP as an internal argument of the verb, using the framework of rhetorical relations. To achieve this goal, we analyse two relevant sources of information: the participle and the connectors. Insofar as the first source, we assess the frequency of regular and irregular participles in the considered corpus, investigate the semantic nature of the participial forms and evaluate their role in inferring the rhetorical relations. As to the second source, we study the semantic value of the connectors and their role in the final reading of the structures under analysis. Finally, we consider the interaction between these two types of information sources.